Three-Dimensional Printing of Hydrogels for Flexible Sensors: A Review - Suhail Ayoub Khan; Hamza Ahmad; Guoyin Zhu; Huan Pang; Yizhou Zhang (Gels, 2024)
The remarkable flexibility and heightened sensitivity of flexible sensors have drawn significant attention, setting them apart from traditional sensor technology. Within this domain, hydrogels—3D crosslinked networks of hydrophilic polymers—emerge as a leading material for the new generation of flexible sensors, thanks to their unique material properties. These include structural versatility, which imparts traits like adhesiveness and self-healing capabilities. Traditional templating-based methods fall short of tailor-made applications in crafting flexible sensors. In contrast, 3D printing technology stands out with its superior fabrication precision, cost-effectiveness, and satisfactory production efficiency, making it a more suitable approach than templating-based strategies. This review spotlights the latest hydrogel-based flexible sensors developed through 3D printing. It begins by categorizing hydrogels and outlining various 3D-printing techniques. It then focuses on a range of flexible sensors—including those for strain, pressure, pH, temperature, and biosensors—detailing their fabrication methods and applications. Furthermore, it explores the sensing mechanisms and concludes with an analysis of existing challenges and prospects for future research breakthroughs in this field.